High delayed mortality after the first episode of Clostridium difficile infection. (June 2019) - ; Romero, José; Muriel, Alfonso; Giner, Livia; Federico, Ferrere; Rocío, Martínez-Ruiz S.; Martos, Purificación; Sardiña, Cristina; Elena, Aguirre; Badía, Cristina; Perales, Alfonso; De Santos-Castro, Pedro A.; et al.
Abstract: Clostridium difficile infection (CDI) is characterized by a high delayed and unrelated mortality. Predicting delayed mortality in CDI patients could allow the implementation of interventions that could reduce these events. A prospective multicentric study was carried out to investigate prognostic factors associated with mortality. It was based on a cohort (July 2015 to February 2016) of 295 patients presenting with CDI. Logistic regression was used and the model was calibrated using the Hosmer-Lemeshow test. The mortality rate at 75 days in our series was 18%. Age (>65 years), comorbidity (defined by heart failure, diabetes mellitus with any organ lesion, renal failure, active neoplasia or immunosuppression) and fecal incontinence at clinical presentation were associated with delayed (75-day) mortality. When present, each of the aforementioned variables added one point to the score. Mortalities with 0, 1, 2 and 3 points were 0%, 9.4%, 18.5% and 38.2%, respectively. The area under the ROC curve was 0.743, and the Hosmer-Lemeshow goodness-of-fit test p value was 0.875. Therefore, the prediction of high delayed mortality in CDI patients by our scoring system could promote measures for increasing survival in suitable cases. Highlights: CDI patients present a high, non-infection related, delayed mortality. Age, comorbidity and fecal incontinence at diagnosis are related to patient outcome. A scoring system based on these variables may predict mortality. Preventive measures could eventually be implemented to improve patient prognoses.